2014
DOI: 10.1155/2014/587823
|View full text |Cite
|
Sign up to set email alerts
|

Selected Factors Determining a Way of Coping with Stress in Type 2 Diabetic Patients

Abstract: Objectives. The aim of the study was to examine factors which determine stress coping styles in type 2 diabetic (T2D) patients, with regard to selected demographic variables, clinical diabetes-related variables and selected psychical variables (anxiety level and assessment of depressive disorders). Methods. 50 T2D patients, aged 59.9 ± 10.2 years were assessed by Coping Inventory for Stressful Situations (CISS), Spielberger State-Trait Anxiety Inventory (STAI), and Beck Depression Inventory (BDI). In the stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…First, the assessment of coping profiles was based on the BSCP, which includes just 18 items, and was developed for Japanese workers and not for people with chronic diseases, such as type 2 diabetes. Several studies have tested different dimensions [7][8][9][10][11][12][13][14][15][31][32][33][34][35][36] . Even for three dimensions, the detailed factors have not yet been integrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the assessment of coping profiles was based on the BSCP, which includes just 18 items, and was developed for Japanese workers and not for people with chronic diseases, such as type 2 diabetes. Several studies have tested different dimensions [7][8][9][10][11][12][13][14][15][31][32][33][34][35][36] . Even for three dimensions, the detailed factors have not yet been integrated.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that: (i) task-oriented coping (problem-focused coping); (ii) emotion-oriented coping (adaptive emotion-focused coping); and (iii) avoidance-oriented coping (maladaptive emotion-focused coping) dimensions are useful based on our clinical experience and previous Japanese research 37 . In addition, there are several questionnaires that have a validated Japanese version, such as the BSCP and the Coping Inventory for Stressful Situations-2nd Edition 34,35 , both of which include the three dimensions mentioned above. Because the BSCP was developed in Japan, it was available in Japan, whereas the Japanese version of the Coping Inventory for Stressful Situations-2nd Edition has only recently been validated 38 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] in reviewing degrees of acceptance in selected chronic diseases, there is a relationship between the level of acceptance of illness among women and men, to the detriment of women. The dependence between the degree of acceptance of a chronic illness and age was also analysed by other authors [ 29 , 30 ]. According to them, this interdependence is determined by the fact that, with age, other ailments escalate, such as degenerative changes in joints, neurological disorders, and motor skill deterioration, even with financial limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the participants’ answers at Week 1 (no 5-ALA), 15 mg and 50 mg of 5-ALA after 12 weeks significantly improved coping ability by 1.5 and 3.2 times, respectively. Diabetes is a stressful, incurable disease that is associated with a higher incidence of depression and anxiety [ 22 ]. For prediabetic adults, the ability to cope with the threat of developing diabetes is important to minimize stress so they can focus on changing their lifestyle.…”
Section: Discussionmentioning
confidence: 99%